Building Capacity to Build Dependency? Institutional Paradoxes in Post 2001 State Building in Afghanistan - Shahida Aman; Shagufta Aman (Journal of Political Studies, 2015)
Beginning in the closing months of 2001, Afghanistan witnessed an international intervention, which started off as a reaction to the security threats from transnational extremist groups and, afterwards blossomed into a full fledged state building exercise. The international state building practice in Afghanistan is guided by the Western notion of a centralized, bureaucratized Weberian state that exercises a monopoly of power over violence within its territory. This conventional top down understanding of state building is in turn, manifested in attempts at constructing security sector apparatuses, a centralized bureaucracy for tax collection and service provision, a robust judiciary patterned on Western lines and political institutions based on liberal democratic model, including a constitution, elections, a civil society and a liberal market economy. The more than a decade long state building intervention has however, failed to improve Afghan state’s coercive capacity, its functional competence in extending services beyond a few urban centres and its democratic legitimacy. Violence, conflict and insurgency have become common place in today’s Afghanistan. This paper argues that the international state building practice is generating institutional paradoxes in Afghanistan and such paradoxes are hampering the attainment of desired state building goals. These paradoxes can be studied within a framework of tribulations in recruitment, training, retention, inadequacy of resources and infrastructural deficiencies, over-centralization without any meaningful devolution or decentralization of authority and finances, coordination dilemmas resulting from multiplicity of actors and agendas, overlapping of functions and responsibilities of state structures and donor assistance to the growth of a second civil service. Such dilemmas are generating institutional paradoxes: international efforts at ‘capacity building’ of formal state institutions are instead generating ‘dependency’ among the state structures. State institutions in post 2001 Afghanistan have grown to become actually more dependent on outside support and funding, carry weak operational capacity, are poorly coordinated, less decentralized and suffer from issues of long term sustainability.